An Outline of Romanticism in the West - Isbell, John Claiborne (Open Book Publishers, 2022)
Navigating the landscape of Romantic literature and art across Europe and the Americas, An Outline of Romanticism in the West invites readers to embark upon a literary journey. Showcasing a breadth of theoretical and contextual approaches to the study of Romanticism, John Isbell provides an insightful contemporary overview of the field, paired with wide-ranging comparative reflections on the art and literature that helped shape it. Discussing seminal Romantic texts such as Mary Shelley's Frankenstein, or Germaine de Staël's Corinne ou l'Italie, Isbell provides a foundation through which to investigate core concepts, such as the continuum of Romance, the Romantic hero, and Romantic literature's characteristic repudiation of its own Romanticism. Unusually for a single-author monograph, the book includes both published and unpublished material covering Romantic creation across Europe and the two Americas. Identifying Romanticism as an international movement, Isbell seeks to emphasise a theme frequently ignored by many academics: the roots of Romanticism, and its variations, as a national art. His arguments are supported by extensive interrogations of the political and historical contexts that moulded the outlooks of the writers and artists central to the period. An Outline of Romanticism in the West underlines the interplay between nationalism, history, and artistic inspiration, and will therefore be of value to students and scholars of literature and history, as well as to general readers with an interest in Romanticism in the West.